MELAS/LS Overlap Syndrome Associated With Mitochondrial DNA Mutations: Clinical, Genetic, and Radiological Studies - Yanping Wei; Yan Huang; Yingmai Yang; Min Qian (Frontiers in Neurology, 2021)
Introduction: Mitochondrial diseases are characterized by considerable clinical and genetic heterogeneity. Mitochondrial encephalomyopathy with lactate acidosis and stroke-like episodes (MELAS) and Leigh syndrome (LS) are both established mitochondrial syndromes; sometimes they can overlap.Methods: A retrospective observational cohort study was done to analyze the clinical manifestations, biochemical findings, neuroimaging and genetic data, and disease outcomes of 14 patients with identified MELAS/LS overlap syndrome.Results: A total of 14 patients, 9 males and 5 females, were enrolled. The median age at onset was 14 years, while the average age was 12.6 years. As for clinical features in concordance with MELAS, the top three most common symptoms were seizures, cognitive impairment, and stroke-like episodes (SLE). Brain atrophy was present in seven patients. As for the clinical hallmarks of LS, the top three most common symptoms were ataxia, spastic paraplegia, and bulbar palsy. Patients presented with individual syndrome or overlap syndromes with similar frequency, and the prognosis did not seem to be related to the initial presentation. Thirteen patients were identified with MTND mutations, among which m.13513G>A mutation in the MT-ND5 gene was the most common. Only one patient with m.8344A>G mutation of MTTK gene was found.Discussion: Our study demonstrated that MTND genes are important mutation hot spots in MELAS/LS overlap syndrome. The follow-up is very important for the final diagnosis of overlap syndrome.